Pengaruh kecemasan dan motivasi belajar terhadap hasil belajar matematika siswa Sekolah Dasar - Ardelia Wardana; Fitri Aida Sari; Sukriadi Sukriadi; Fara Virgianita Pangadongan; Maria Donata Mariani Priyambodo (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2026)
This study aims to analyse the influence of mathematics anxiety and learning motivation on the mathematics learning outcomes of sixth-grade students at an elementary school in Samarinda City. The research employed a quantitative, correlational design. A total of 56 students participated as research subjects using a total sampling technique. Data were collected through a mathematics anxiety questionnaire, a learning motivation questionnaire, interviews, and documentation of the final exam scores. Data analysis was conducted using multiple linear regression after confirming the assumptions of normality, multicollinearity, and heteroscedasticity. The results showed that mathematics anxiety did not have a significant effect on learning outcomes (Sig. = 0.118 ≥ 0.05), whereas learning motivation did (Sig. = 0.004 ≤ 0.05). Simultaneously, both variables had a significant effect, contributing 23.1% to mathematics learning outcomes. Learning motivation was found to be the most dominant factor. From the interviews, other factors influencing learning outcomes were identified, including family and school environments, teaching methods, and students’ study habits. The findings imply that teachers should analyse students’ characteristics to design adaptive instruction that optimises learning outcomes